A rapid screening method for a single nucleotide polymorphism (SNP) in the human MOR gene - Grösch, Sabine (Blackwell Science Inc, 2001)
AIMS: Genetic association studies have suggested that the single nucleotide polymorphism (SNP) at position 118 of the human µ-opioid receptor (MOR) gene could be a potential risk factor for drug treatment variability in patients. Therefore, we wanted to develop a fast and reliable detection method for this SNP which is applicable in a clinical setting. METHODS: To detect the polymorphism at position A118→G in the human MOR gene we used the fluorescence resonance energy transfer (FRET)-PCR technique with subsequent melting curve analysis. RESULTS: The polymorphism at position A118→G in the human MOR gene could be clearly discriminated with melting peak temperatures of 69.8 ° C and 63.8 ° C, corresponding to the wild type and mutated MOR allele, respectively. The results from FRET-PCR were validated by sequencing and restriction-fragment length polymorphism (RFLP). Screening of blood samples from 100 subjects showed an allelic distribution for the human MOR alleles of 79% (homozygous wild type), 20% (heterozygous) and 0.9% (homozygous mutated). CONCLUSIONS: The FRET-PCR protocol for detection of the human MOR gene polymorphism at position 118 offers a rapid and reliable method which could be used for population screening of this and other genes.